The making of the modern police, 1780-1914.
1 online resource (1552 pages).
Keywords: Over six volumes this edited collection of pamphlets, government publications, printed ephemera and manuscript sources looks at the development of the first modern police force. It will be of interest to social and political historians, criminologists and those interested in the development of the detective novel in nineteenth-century literature.